The Effectiveness of SPENZALA TenseSmart (STS) in Improving Students’ Mastery of English Tenses - Usriyah, Endang; Egar, Ngasbun; Sukmaningrum, Rahmawati (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2025)
This study investigates the effectiveness of the SPENZALA TenseSmart (STS) application in improving ninth-grade students’ mastery of English tenses. Employing a one-group pre-test–post-test design within a blended learning environment, the study involved 31 students from Class IX A at SMP Negeri 1 Welahan. Data were collected using a pre-test, post-test, and a student response questionnaire. The results indicate a substantial improvement in students’ grammar achievement, with the mean score increasing from 59.58 to 85.16. The normalized gain (N-gain) value falls into the moderate-to-high category, confirming the effectiveness of the intervention. A paired sample t-test further shows a statistically significant difference between the pre-test and post-test results (p 0.05). Student responses also demonstrate highly positive perceptions of the STS application (overall mean = 4.36), particularly regarding flexibility, ease of use, and usefulness for mastering tenses. The findings suggest that STS is an effective digital learning tool that enhances grammar understanding, supports independent learning, and increases motivation within a blended learning context.